INTERPLAY OF SELF CONFIDENCE AND ORAL COMMUNICATION OF ENGLISH LEARNERS - Buhari, Buhari; Hanafi, Muhammad (Uniqbu Journal of Social Sciences, 2022)
This Article aims to describe whether there is a relationship between students 'self-confidence with students' oral ability. This research uses cluster sumpling method and oral test. The population in this research is the students of class VII SMPN 9 Pinrang. The total population is 104 students. The sample used is class VIIL.1 amounted to 28 students. The method used in the assessment of speech is an oral test. Result of research by using Pearson Product Moment obtained r value count 0,700 and with value of product r product moment product with N = 28 found 0,478 at significant level 1% and found 0,374 at level signifikan5%. And to know the level of product moment correlation then coefficient 0.61-0.80 = substantial.Thus it can be interpreted to the rxy that between variable X and variable Y. It can be seen on the analysis result that is: 0,700> 0,478 (5%) and 0,700 0,374 (1%) with d.b:28. This means Ho is rejected and Ha accepted. The conclusion in this study is there is a significant relationship between student self-confidence and oral ability of eight-year students SMPN 9 Pinrang.